Effect of Microvascular Invasion on the Prognosis in Hepatocellular Carcinoma and Analysis of Related Risk Factors: A Two-Center Study - Yanhan, Wang; Lianfang, Lu; Hao, Liu; Yunfeng, Ding; Nannan, Song; Fanfan, Lin; Chengzhan, Zhu; Meilong, Wu; Chuandong, Sun (Frontiers in Surgery, 2021)
Objective: Microvascular invasion (MVI) is considered to initiate intrahepatic metastasis and postoperative recurrence of hepatocellular carcinoma (HCC). We aimed to analyze the effect of MVI on the prognosis in HCC and identify related risk factors for MVI. Methods: The clinical data of 553 HCC patients who underwent liver surgery at Qingdao University from January 2014 to December 2018 and 89 patients at Beijing Tsinghua Changgung Hospital treated between October 2014 and October 2019 were collected retrospectively. We explored the impact of MVI on the prognosis of patients with HCC using Kaplan-Meier analysis. To identify variables significantly related to MVI, we conducted a logistic regression analysis. Results: Pathological examination confirmed the presence of MVI in 265 patients (41.3%). Six factors independently correlated with MVI were incorporated into the multivariate logistic regression analysis: Edmondson-Steiner grade (odds ratio [OR] =3.244, 95% confidence interval [CI]: 2.243-4.692; p<0.001), liver capsule invasion (OR=1.755; 95%CI: 1.215–2.535; p=0.003), bile duct tumor thrombi (OR=20.926; 95%CI: 2.552–171.553; p=0.005), α-fetoprotein (>400 vs. <400 ng/ml; OR=1.530; 95%CI: 1.017–2.303; p=0.041), tumor size (OR=1.095; 95%CI: 1.027–1.166; p=0.005), and neutrophil-lymphocyte ratio (OR=1.086; 95%CI: 1.016–1.162; p=0.015). The area under the receiver operating characteristic curve was 0.743 (95%CI: 0.704-0.781; p<0.001), indicating that our logistic regression model had significant clinical usefulness. Conclusions: We analyzed the effect of MVI on the prognosis in HCC and evaluated the risk factors for MVI, which may be useful in making decisions regarding clinical treatment.